Integrating the needs of recovering populations of baleen whales into the revised management framework for the commercial fishery for Antarctic krill - Trathan, Philip N.; Savoca, Matthew S.; Friedlaender, Ari; Baines, Mick; Burkhardt, Elke; Cheeseman, Ted; Dalla Rosa, Luciano; Herr, Helena; Secchi, Eduardo R.; Zerbini, Alexandre N.; Reisinger, Ryan R. (Frontiers in Marine Science, 2024)
We consider how the ongoing recovery of baleen whale populations requires improved understanding when managing the largest commercial fishery in the Southern Ocean, the fishery for Antarctic krill. Baleen whales already represent one of the major consumers of krill, and as such compete with the fishery. However, they are not explicitly included either in the monitoring programme or the krill fisheries management approach of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR). Individual baleen whales are at direct mortality risk from ship strike, entanglement, or by-catch. In addition, sub-lethal impacts on individuals, albeit with population-level consequences, via decreased body condition and reproductive rates, may arise from local depletion of prey and prey-field disturbance that increases whale energetic costs. Mitigating these risks requires that baleen whales, including those species not yet recovered, are fully integrated into management procedures. A vital issue will be to facilitate the ongoing recovery of blue, fin and sei whales, populations of which are still heavily depleted relative to their pre-whaling abundance. Part of the answer to this will be how CCAMLR resolves outstanding issues related to its newly emerging revised krill fishery management framework. Management of the krill fishery is data-poor, with much of the scientific support reliant upon data that are now decades old. The decision rules for determining sustainable yields need careful re-evaluation, given they were negotiated at a time when baleen whales were rarely observed, and krill fishery catches were low in relation to the estimated available krill biomass. The Antarctic marine ecosystem is spatially and temporally dynamic, and is changing, yet CCAMLR still assumes a static system. An explicit commitment to collect up-to-date monitoring data about krill and baleen whales is vital to help inform the revised management framework. Precaution argues that catch levels should not increase until adequate data are available for effective management. Knowledge about the status of baleen whales will inevitably require close collaboration with the International Whaling Commission.